Report of the Study Team on Tribal Research Institutes - Planning Commission (Planning Commission, 1972)
The Panel on Welfare of Backward Classes constituted by the Planning Commission in 1968 to advise on the formulation of the Fourth Five Year Plan for the welfare of backward classes recommended that the Planning Commission might take steps to constitute a Study Term to examine various aspects pertaining to the working of the tribal research institutes including enlargement, of the scope of their active ties and the setting up of a Central Research Institute.
Planning Commission Government of India
Planning Commission Government of India